(untitled) (diségno, 2024)
Since time immemorial, Drawing has been the visual language of all activities related to the world of building. It allows for the prefiguration, configuration, realisation and critical analysis of construction. Among its applications is the analogue scale model, which represents a tangible expression of design thinking However, what happens when the object in question is not a work of architecture, but rather a single structural component of a building or an engineering artefact? This paper offers an analysis of models representing the structural essence of architectural and engineering artefacts. It examines artefacts from an academic collection (second half of the 19th century), the scientific work of G. Curioni. The collection consists of more than 140 models designed as scientific supports for the didactics of Structural Mechanics and Engineering, a field in which Curioni was a prominent figure in Italy. The research represents a potential avenue for the university’s Third Mission, namely the dissemination and dissemination of knowledge about the Curioni Collection. This is achieved by creating a virtual museum that hosts the virtual models of the collection in different sharing environments, with the aim of reaching as many users as possible. The model becomes a communication tool brought up to date through the reinterpretation and reinterpretation of manuals and models, transforming the material artefact into a virtual model and introducing new forms of representation.